Pathogenic variability of Plasmopara halstedii infecting sunflower in the Czech Republic. (27th June 2017) - Drábková Trojanová, Z.; Sedlářová, M.; Pospíchalová, R.; Lebeda, A.
Abstract : Plasmopara halstedii was isolated from diseased sunflowers collected from eight locations in the Czech Republic from 2007 to 2014. Races of the pathogen were determined based on 84 isolates collected during the study. In total, eight races of P. halstedii were detected using a set of nine sunflower differential lines. Races 700, 704, 705, 710, 714 and 715 were proven by soil drench inoculation, and two additional races (730 and 770) proposed by the previously applied leaf disc inoculation method. Race 700 was the most dominant in the Czech P. halstedii populations, with race 710 being the second most frequent. Races 704 and 714 were found over three seasons, while other races were recorded only in one growing season (race 730 in 2010, and the new races 705 and 715 in 2014). A comprehensive study was further conducted for isolates collected in 2013–14 using an extended differential set consisting of 15 sunflower lines. According to the latter methodology which marks races with five‐digit virulence codes, races 70060, 70471, 70571, 71060, 71461 and 71571 were recorded. The growing complexity of P. halstedii pathogenicity exhibited by the ability to infect higher numbers of differential genotypes and resulting in determination of the new pathogen races (virulence profiles) 70571, 71461 and 71571 is alarming. Although the limited number of isolates studied cannot characterize the entire pathogen diversity in the Czech Republic, the trend towards more diverse virulence in P. halstedii populations is clearly demonstrated by the new records of races 704, 705, 714 and 715, all capable of overcoming the resistance gene Pl 6 .